Flavouring Group Evaluation 413 (FGE.413): Naringenin - EFSA Panel on Food Additives and Flavourings (FAF); Maged Younes; Gabriele Aquilina; Laurence Castle; Gisela Degen; Karl‐Heinz Engel; Paul J. Fowler; Maria José Frutos Fernandez; Peter Fürst; Ursula Gundert‐Remy; Rainer Gürtler; Trine Husøy; et al. (EFSA Journal)
Abstract The EFSA Panel on Food Additives and Flavourings (FAF) was requested to evaluate the safety of naringenin [FL‐no: 16.132] as a new flavouring substance, in accordance with Regulation (EC) No 1331/2008. No other substances with sufficient structural similarity have been identified in existing FGEs that could be used to support a read‐across approach. The information provided on the manufacturing process, the composition and the stability of [FL‐no: 16.132] was considered sufficient. From studies carried out with naringenin, the Panel concluded that there is no concern with respect to genotoxicity. The use of naringenin as a flavouring substance at added portions exposure technique (APET) exposure levels is unlikely to pose a risk for drug interaction. For the toxicological evaluation of naringenin, the Panel requested an extended one‐generation toxicity study on naringenin, in line with the requirements of the Procedure and to investigate the consequence of a possible endocrine‐disrupting activity. The Panel considered that changes in thymus weight, litter size, post‐implantation loss and a consistent reduced pup weight in the high‐dose F2 generation could not be dismissed and selected therefore, the mid‐dose of 1320 mg/kg body weight (bw) per day for the parental males as the no observed adverse effect level (NOAEL) of the study. The exposure estimates for [FL‐no: 16.132] (31,500 and 50,000 μg/person per day for children and adults, respectively) were above the threshold of toxicological of concern (TTC) for its structural class (III). Using the NOAEL of 1320 mg/kg bw per day at step A4 of the procedure, margins of exposure (MoE) of 1590 and 630 could be calculated for adults and children, respectively. Based on the calculated MoEs, the Panel concluded that the use of naringenin as a flavouring substance does not raise a safety concern.